2019
DOI: 10.1101/549568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Propagating patterns of activity across motor cortex facilitate movement initiation

Abstract: Voluntary movement initiation involves the modulation of neurons in the primary motor cortex (M1) around movement onset. Yet, similar modulations of M1 activity occur during movement planning when no movement occurs. Here, we show that a sequential spatio-temporal pattern of excitability based on beta oscillation amplitude attenuation propagates across M1 prior to the initiation of reaching movements in one of two oppositely oriented directions along the rostrocaudal axis. Using spatiotemporal patterns of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Yet another effort is pursued to also analyze the characteristics of wave-like phenomena in other frequency regimes. For example, in alpha, beta, and gamma frequency ranges, diverse and complex wave patterns have been observed in various experiments of awake behaving animals (Balasubramanian et al, 2019;Denker et al, 2018b;Petersen et al, 2003;Senseman and Robbins, 2002;Townsend and Gong, 2018;Wu et al, 2008). A pipeline approach similar to the Cobrawap may disentangle and align some of the various reported results, methods, and terminologies.…”
Section: Re-usability: Related Pipelines and Outlookmentioning
confidence: 99%
“…Yet another effort is pursued to also analyze the characteristics of wave-like phenomena in other frequency regimes. For example, in alpha, beta, and gamma frequency ranges, diverse and complex wave patterns have been observed in various experiments of awake behaving animals (Balasubramanian et al, 2019;Denker et al, 2018b;Petersen et al, 2003;Senseman and Robbins, 2002;Townsend and Gong, 2018;Wu et al, 2008). A pipeline approach similar to the Cobrawap may disentangle and align some of the various reported results, methods, and terminologies.…”
Section: Re-usability: Related Pipelines and Outlookmentioning
confidence: 99%
“…They suggest that these waves can modulate the excitability of the cortex in such a way as to affect processing of future stimuli. More recently, [16] have suggested that propagating waves in motor cortex can facilitate the initiation of movement and [17] have shown that spontaneous propagating waves can affect perception in awake monkeys. Because of their possible roles in modulating cortical excitability in a spatially and temporally precise manner, it is important to better understand the cellular mechanisms that control these waves.…”
Section: Introductionmentioning
confidence: 99%